Effect of recomposted button mushroom spent substrate on the yield of wheat (Triticum destivum L.) - Ahlawat, O P; Sagar, M P; Raj, Dev; Gupta, Pardeep; Vijay, B (Mushroom Research, 2015)
Please see the full text